Pemanfaatan Ekonomi Digital Dalam Strategi Pemasaran Dan Pelayanan Pada Usaha Kuliner UMKM Di Masa Pandemi Covid-19 Serta Strategi Adaptasi Di Era New Normal - Andri Juniansyah (Universitas Nusa Putra, 2022)
The COVID-19 pandemic which has an impact on the economy around the world, especially in Indonesia, has caused the situation to become unstable. The impact of this pandemic has severely hit Micro, Small and Medium Enterprises (MSMEs), especially in the culinary industry, which have difficulty in carrying out their sales activities, with the enactment of regulations from the government regarding Large-Scale Social Restrictions. (PSBB) in 2020 and continued with the Implementation of Community Activity Restrictions (PPKM) in 2020. 2021, making many MSME culinary business actors try in various ways to be able to market their products and maintain their business. By utilizing internet technology that is growing rapidly and supported by social media applications and online ordering which has become a lifestyle of the community, this is very helpful for MSME culinary business actors and also the community in the midst of limited activity so that buying and buying and selling transaction services in the culinary industry can goes well. . This study aims to determine the use of the digital economy in marketing and service strategies for MSME culinary business actors during the COVID-19 pandemic and adaptation strategies in the new normal era (case study on Dimsum Likeearth, Sukabumi City).